Pola Kemitraan dan Pendapatan Peternak di KPT Maju Sejahtera Kecamatan Tanjung Sari Kabupaten Lampung Selatan - Jazim, Fahriza Anjaya; Rufaidah, Erlina; Indriani, Yaktiworo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The purposes of this research are to: ascertain the pattern, mechanisms, rights and responsibilities, and evaluation of partnerships carried out by KPT Maju Sejahtera; analyze the income of both partner and non-partner cattle breeders; in addition to analyze the variables influencing breeders choices to form partnerships. The research location was chosen purposively, taking into account that KPT Maju Sejahtera has been running a partnership program since 2017 and that South Lampung District is one of the population centres or beef cattle areas in Lampung Province. About 66 participants were chosen at random to participate in the research as respondents. The months of January through February in 2024 were used for data collection.  The analysis method used to answer the first purpose was descriptive qualitative analysis; farming business analysis was used to answer the second; and binary logistic regression analysis was used to answer the third. The results showed that KPT Maju Sejahtera and IACCB had formed an agribusiness operational cooperation patternship pattern. The evaluation results of the partnership established between IACCB and KPT Maju Sejahtera showed that the partnership was going well in accordance with the agreed cooperation agreement. The average income for livestock business in Tanjung Sari sub-district was IDR 19.906.090,91 for partners and IDR 14.820.030,30 for non partner breeders. Breeders’ decisions to partner are influenced more positively by factors like age, education, and income.